2022
DOI: 10.1155/2022/4652326
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Resistance of Bacteria Isolated from Marine and Freshwater Fish in Tanzania

Abstract: This study aimed to determine the prevalence and antimicrobial resistance of bacteria isolated from retail fish and shrimp in Tanzania. A total of 92 fish and 20 shrimp samples were analyzed. Fish samples consisted of 24 Nile tilapia, 24 Nile perch, and 24 red snapper. The isolates were identified by their morphological characteristics, conventional biochemical tests, and analytical profile index test kits. The antibiotic susceptibility of selected bacteria was determined by the disc diffusion method. Out of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
2
14
2
Order By: Relevance
“…However, no ESBL-producing E. coli was recovered from Rohu fish from Myanmar (0%). Similar to other reports, a high prevalence (36.0%) of E. coli compared to other bacteria was found in marine and freshwater fish samples derived from retail markets in Dar es Salaam, Tanzania [ 25 ]. The prevalence of E. coli has also been found in tropical seafood including finfish, shrimp, oysters, and clams.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, no ESBL-producing E. coli was recovered from Rohu fish from Myanmar (0%). Similar to other reports, a high prevalence (36.0%) of E. coli compared to other bacteria was found in marine and freshwater fish samples derived from retail markets in Dar es Salaam, Tanzania [ 25 ]. The prevalence of E. coli has also been found in tropical seafood including finfish, shrimp, oysters, and clams.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have reported the prevalence of Salmonella from various fish sources, the main ingredient of fish meal production. From the previous report, the highest prevalence of Salmonella was observed from Nile perch (26%), followed by Nile tilapia (24%) and red snapper (12%) collected from the retail market in Dar es Salaam, Tanzania [ 25 ]. Out of 238 fish samples, 57 (24%) collected from Ouagadougou, Burkina Faso showed the positive result for Salmonella detection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in marine mammals, including different bacterial species, reported the presence of resistant isolates in 35% to 74% of the investigated samples [ 83 , 84 , 86 , 88 ]. No antimicrobial-resistant E. coli was obtained from the fish samples collected in this study, although resistant E. coli has been isolated from different marine fish species in other studies [ 40 , 44 ].…”
Section: Discussionmentioning
confidence: 95%
“…Once these microbes and antimicrobial residues are released into the environment, natural water bodies themselves may play a certain role in the persistence, emergence, and spread of antimicrobial resistance [ 38 ]. However, antimicrobial-resistant bacteria have also been found in various marine species of all taxa [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. For surveillance, apex predators like marine mammals are of specific interest, as they may mirror the burden of antimicrobial resistance in the marine food web as well as the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, none of the S. aureus was resistant to gentamicin. In the study conducted by Marijani, [ 66 ], among 16 S. aureus isolates, 31% and 5% were resistant to tetracycline and gentamicin, respectively. However, a resistance to ciprofloxacin, clindamycin, and penicillin was observed in 19%, 13%, and 13% of isolates, respectively.…”
Section: Discussionmentioning
confidence: 99%